The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1063/1.475319
|View full text |Cite
|
Sign up to set email alerts
|

H 2 S adsorption on chromium, chromia, and gold/chromia surfaces: Photoemission studies

Abstract: The reaction of H 2 S with chromium, chromia, and Au/chromia films grown on a Pt͑111͒ crystal has been investigated using synchrotron-based high-resolution photoemission spectroscopy. At 300 K, H 2 S completely decomposes on polycrystalline chromium producing a chemisorbed layer of S that attenuates the Cr 3d valence features. No evidence was found for the formation of CrS x species. The dissociation of H 2 S on Cr 3 O 4 and Cr 2 O 3 films at room temperature produces a decrease of 0.3-0.8 eV in the work funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 63 publications
4
47
0
Order By: Relevance
“…The adsorption energy of sulfur atom on Mo 2 C(001) surface is weaker than that on Mo(100) of 185.85 kcal/mol, while much stronger than that on Fe(100) of 66.74 kcal/mol [14]. These results are also consistent with the experiment observations that S atoms remain on the surface even for the temperatures in excess of 800 K [55][56][57]. The binding energy between S and Mo 2 C(001) surface is much stronger than that SH/Mo 2 C(001) and H 2 S/Mo 2 C(001) (77.20 kcal/mol, 26.12 kcal/mol, respectively) at their most stable adsorption sites, indicating that the thermodymic driving force is large for H 2 S dissociation on Mo 2 C(001) surface.…”
Section: Speciessupporting
confidence: 92%
See 1 more Smart Citation
“…The adsorption energy of sulfur atom on Mo 2 C(001) surface is weaker than that on Mo(100) of 185.85 kcal/mol, while much stronger than that on Fe(100) of 66.74 kcal/mol [14]. These results are also consistent with the experiment observations that S atoms remain on the surface even for the temperatures in excess of 800 K [55][56][57]. The binding energy between S and Mo 2 C(001) surface is much stronger than that SH/Mo 2 C(001) and H 2 S/Mo 2 C(001) (77.20 kcal/mol, 26.12 kcal/mol, respectively) at their most stable adsorption sites, indicating that the thermodymic driving force is large for H 2 S dissociation on Mo 2 C(001) surface.…”
Section: Speciessupporting
confidence: 92%
“…The bonding of the H 2 S to the surface involves mainly the interaction of the sulfur lone-pair orbital with the surface Mo atom. The transfer of electrons from the surfaces into the LUMO of H 2 S is minimal due to the high energy of this molecular orbital [55]. While the electrons transferred from the sulfur's lone-pair orbital to the surface are larger than those to the surface.…”
Section: Speciesmentioning
confidence: 98%
“…Collaborative density functional theory calculations revealed that SO2 dissociation was greatly enhanced on gold when the particle is located above an oxygen vacancy. Rodriguez and co-workers found further evidence of support effects in their comparison of SO2 adsorption on Au/TiO2 as compared to Au/MgO (361). In the case of MgO as a support, no dissociation of SO2 was observed, although the desorption temperature was much higher than that of SO2 from an Au single crystal.…”
Section: 3mentioning
confidence: 91%
“…The 0.53 eV electron Schottky barrier measured in this work is in relatively close agreement with previous DFT predictions of electron Schottky barrier magnitude for Au contacts to monolayer (0.58 eV) and bilayer (0.66 eV) WSe 2 [8] [31] and Cr x Se y (Φ Cr2Se3 = 5.15 eV) [68] present at the Cr-WSe 2 interface could result in a similar FL position. Although no Cr x O y is detected following Cr deposition under UHV conditions, the electronic structure of chromium oxide varies substantially with composition [68][69][70] and therefore is likely to appreciably affect the FL position when Cr is deposited under HV conditions. Recently, n-type conduction has been reported for Cr contacts (HV) to multi-layer WSe 2 -based devices in contrast with the band alignment obtained in this work between WSe 2 and Cr deposited under UHV conditions [71].…”
Section: Cr-wse 2 : Substantial Oxidation Of Low-φ Metal and Associatmentioning
confidence: 99%